Glucose-6-phosphate dehydrogenase deficiency with coinherited Gaucher disease: A rare association - Nupur Parakh; Kusha Sharma; Sunita Sharma; Priti Chatterjee; Varinder Singh (Indian Journal of Pathology and Microbiology, 2024)
Anemia coexisting with Gaucher disease (GD) is often associated with non-hemolytic processes. Few cases of GD with autoimmune hemolytic anemia have been reported. However, literature on GD with concomitant nonimmune hemolytic anemia is scarce. A 1-year 6-month-old male child presented in 2018 with complaints of palpable mass in left upper abdomen, fever, cough, and vomiting. On examination, he had pallor, hepatosplenomegaly of 2 cm and 8 cm below costal margin, respectively. A clinical diagnosis of hemolytic anemia was suspected. Complete blood count revealed Hb---6.7 g/dL, TLC---8.9 × 103/μL, platelet count---180 × 103/μL. Peripheral smear showed predominantly microcytic hypochromic anemia with moderate degree of anisocytosis, many nucleated red blood cells, few schistocytes, polychromatophils and corrected reticulocyte count 7.89%. S. Bilirubin was 1.1 mg/dL. Hb high-performance liquid chromatography (HPLC) of the child and his parents was within normal limit. Hematological work up revealed negative results for direct Coombs’ test, osmotic fragility test, and sickling test. Test for Glucose-6-phosphate dehydrogenase deficiency was positive (39 units/trillion RBC, normal 146--376). He was transfused intermittently and given steroids to manage his anemia. He was on regular follow up during which his blood counts revealed persistent anemia and thrombocytopenia. In view of this, bone marrow was performed to exclude myelofibrosis. Aspirate smears were cellular and showed normoblastic erythroid hyperplasia. Numerous large histiocytes with basophilic fibrillary cytoplasm exhibiting “crumpled tissue paper” appearance were seen. Similar findings were seen on bone marrow trephine biopsy. Genetic testing revealed pathogenic variations in the GBA gene. Beta glucosidase enzyme levels were low while chitotriosidase was raised (1109.19 nmol/hr/mL). A final diagnosis of G6PD with GD was made. The present study shows rare association of GD with Glucose-6-phosphate dehydrogenase deficiency.